Is the Knowledge‑intensive Business Services Sector Crisis‑robust or Crisis‑resilient? A Comparative Study of European Union Countries - Wyszkowska‑Kuna, Joanna (Comparative Economic Research. Central and Eastern Europe, 2023)
The paper examines the crisis robustness and resilience of the knowledge‑intensive business services (KIBS) sector. The hypothesis is tested that the KIBS sector is crisis‑robust rather than crisis‑resilient. The study covers 2000–2021, divided into two crisis periods (the global financial crisis and the COVID–19 pandemic) and three non‑crisis periods. The growth rates of value added and employment for the sectors and periods covered by the study are compared. The study is based on data from Eurostat, and it refers to the EU–27, making it possible to carry out comparative research between EU countries, as well as between the EU members before 2004 (i.e., the EU–14 or ‘old’ members) and those who joined in 2004 or later (i.e., the EU–13 or ‘new’ members). The study contributes to the literature by demonstrating that it is necessary to distinguish between the concepts of crisis resilience and crisis robustness in both scientific research and policy strategies, as well as to pay more attention to the issue of crisis robustness. It also makes a contribution by indicating that KIBS have significant potential to contribute to building crisis resilience and crisis robustness in the companies that use them and in the whole economic system. The empirical results demonstrate that the KIBS sub‑sectors, i.e., computer and information services and professional, scientific and technical services, are crisis‑robust, which is not the case for the manufacturing sector. The KIBS sector’s ability to maintain stable growth during crisis periods is more visible than for other service industries. The Polish sector of professional, scientific and technical services showed the most stable upward trend through all analysed periods. Poland also recorded impressive growth in value added in computer and information services during the pandemic period, but when considering the whole period, other countries achieved better results, e.g., Romania.